Genetic enhancement: an avenue to combat aging-related diseases. (22nd November 2022) - Cai, Yusheng; Ji, Zhejun; Wang, Si; Zhang, Weiqi; Qu, Jing; Belmonte, Juan Carlos Izpisúa-; Liu, Guang-Hui
Abstract: Aging is a major risk factor for multiple diseases, including cardiovascular diseases, neurodegenerative disorders, osteoarthritis, and cancer. It is accompanied by the dysregulation of stem cells and other differentiated cells, and the impairment of their microenvironment. Cell therapies to replenish the abovementioned cells provide a promising approach to restore tissue homeostasis and alleviate aging and aging-related chronic diseases. Importantly, by leveraging gene editing technologies, genetic enhancement, an enhanced strategy for cell therapy, can be developed to improve the safety and efficacy of transplanted therapeutic cells. In this review, we provide an overview and discussion of the current progress in the genetic enhancement field, including genetic modifications of mesenchymal stem cells, neural stem cells, hematopoietic stem cells, vascular cells, and T cells to target aging and aging-associated diseases. We also outline questions regarding safety and current limitations that need to be addressed for the continued development of genetic enhancement strategies for cell therapy to enable its further applications in clinical trials to combat aging-related diseases.